Incretin-Based Therapies and Cancer: What’s New? - Sanja Medenica; Jelena Bogdanovic; Jelena Vekic; Tanja Vojinovic; Ivana Babic; Ljiljana Bogdanović; Viviana Maggio; Mohamed El Tanani; Manfredi Rizzo (Medicina)
Growing interest in incretin-based therapies for diabetes mellitus has led to an increased evaluation of their potential effects on cancer development. This review aims to synthesize recent evidence regarding the relationship between incretin-based therapies and cancer risk. We conducted a comprehensive literature review focusing on studies investigating dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists, and dual GLP-1/glucose-dependent insulinotropic polypeptide (GIP) receptor agonists in relation to various malignancies. Current findings suggest that while these therapies demonstrate potential benefits, including weight reduction and metabolic regulation, concerns remain regarding their long-term safety profile. Notably, some studies indicate an increased risk of thyroid and pancreatic cancers, while others report protective effects against prostate, colorectal, and breast cancers. Given the complexity of their effects, further long-term studies and post-marketing surveillance are warranted. This review highlights the need for careful clinical assessment when prescribing incretin-based therapies to patients who may be at increased risk of cancer.